Investigations on anopheline mosquitoes close to the nest sites of chimpanzees subject to malaria infection in Ugandan Highlands - Krief Sabrina; Levrero Florence; Krief Jean-Michel; Thanapongpichat Supinya; Imwong Mallika; Snounou Georges; Kasenene John M; Cibot Marie; Gantier Jean-Charles (Malaria Journal, 2012)
Abstract Background Malaria parasites (Plasmodium sp.), including new species, have recently been discovered as low grade mixed infections in three wild chimpanzees (Pan troglodytes schweinfurthii) sampled randomly in Kibale National Park, Uganda. This suggested a high prevalence of malaria infection in this community. The clinical course of malaria in chimpanzees and the species of the vectors that transmit their parasites are not known. The fact that these apes display a specific behaviour in which they consume plant parts of low nutritional value but that contain compounds with anti-malarial properties suggests that the apes health might be affected by the parasite. The avoidance of the night-biting anopheline mosquitoes is another potential behavioural adaptation that would lead to a decrease in the number of infectious bites and consequently malaria. Methods Mosquitoes were collected over two years using suction-light traps and yeast-generated CO2 traps at the nesting and the feeding sites of two chimpanzee communities in Kibale National Park. The species of the female Anopheles caught were then determined and the presence of Plasmodium was sought in these insects by PCR amplification. Results The mosquito catches yielded a total of 309 female Anopheles specimens, the only known vectors of malaria parasites of mammalians. These specimens belonged to 10 species, of which Anopheles implexus, Anopheles vinckei and Anopheles demeilloni dominated. Sensitive DNA amplification techniques failed to detect any Plasmodium-positive Anopheles specimens. Humidity and trap height influenced the Anopheles capture success, and there was a negative correlation between nest numbers and mosquito abundance. The anopheline mosquitoes were also less diverse and numerous in sites where chimpanzees were nesting as compared to those where they were feeding. Conclusions These observations suggest that the sites where chimpanzees build their nests every night might be selected, at least in part, in order to minimize contact with anopheline mosquitoes, which might lead to a reduced risk in acquiring malaria infections.